Genetic population structure of the Blackspot seabream (Pagellus bogaraveo): contribution of mtDNA control region to fisheries management. (19th May 2021) - Robalo, Joana I.; Farias, Inês; Francisco, Sara M.; Avellaneda, Karen; Castilho, Rita; Figueiredo, Ivone
Abstract: Marine fisheries management models have traditionally considered biological parameters and geopolitical boundaries. The result is the existence of fisheries management units that do not match genetic populations. However, this panorama is changing with the contribution of genetic and genomic data. Pagellus bogaraveo is a commercially important sparid in the northeast Atlantic, with three stock components being considered by ICES: the Celtic Sea and Bay of Biscay, Atlantic Iberian waters and the Azores. The northern stock collapsed (1975–1985) and is essential to characterize the genetic makeup of the species, particularly in the Iberian Peninsula, where it is managed as a single stock. The mitochondrial control region was used to screen the intraspecific diversity and population structure of individuals from six locations across the species range. The genetic diversity found is similar among sites, and there is differentiation between the Azores and the remaining locations.